Zakonodavno-iravnioš funkcionalen jošsšyl niz irimeri odmakedonskioš jazik - Tanturovska, Lidim (Stylistyka, 2021)
In this article we are analysed the acts of Parliament in Republic of Macedonia. They are included in THE ADMINISTRATIVE STYLE WITH EMPHASIS ON THE LEGISLATIVE TEXTS IN MACEDONIAN. We concluded that the cliche is the generał characteristic and we are tried to present the main language characteristics.